Projected heatwaves in Xinjiang Uygur autonomous region, China - Dong, Diwen; Tao, Hui; Zhang, Zengxin; Mondal, Sanjit Kumar (Frontiers in Earth Science, 2024)
Introduction: Heatwaves (HWs) are the serious natural disaster that exert great impacts on human health and social economy. Projecting future changes in HWs is crucial for the development of effective adaptation strategies. Method: This study investigates the variations of HWs in Xinjiang for three time periods (near-term, mid-term, and long-term) under four Shared Socioeconomic Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5) using multi-model ensemble (MME). To enhance confidence in HWs projection, we evaluate the performance of 17 climate models in simulating HWs in terms of interannual variability and spatial patterns using interannual variability skill score (IVS) and distance between indices of simulation and observation (DISO), respectively, and generate MME using the overall performance. Results: Compared to the observed data, the overall performance of MME outperforms most of individual models, although many models effectively capture the characteristics of HWs. Projections indicate that HWs in Xinjiang will become more longer lasting and severe. Specifically, heatwave frequency (HWF) and heatwave duration (HWD) are projected to reach 7.5 times and 61 days, respectively, in the long-term under the SSP5-8.5 scenario. The spatial distribution of HWs exhibits significant heterogeneity, with high value regions primarily distributed in eastern Xinjiang and the eastern part of southern Xinjiang. Although the HWs area is projected to expand under all scenarios, the spatial pattern is anticipated to remain largely unchanged. Conclusion: These findings provide a comprehensive assessment of future variations in HWs, which are necessary for improving regional adaptive capacity to extreme heat risk.